SHE, ROBOT: MALE CHARACTERS’ MECHANISATION OF OPHELIA IN SHAKESPEARE’S HAMLET - Zanyar Faiq Saeed (Universitas Islam Sumatera Utara (UISU), 2021)
This paper entitled “She, Robot: Male Characters’ Mechanisation of Ophelia in Shakespeare’s Hamlet” is an attempt to explain how Ophelia is deprived of her subjectivity and objectified into a machine-like being that cannot think, speak, and act independently. The agents of this mechanisation are three male characters, namely, Laertes, Polonius and Hamlet respectively. The paper traces the mechanisation process by expounding how each one of the male characters, thinking himself superior, commanding and abusing Ophelia until she turns into a broken machine. This may be considered as one of the major reasons behind her mental breakdown and, ultimately, her supposed suicide. The organisation of the text is based on the successive roles of each of the above-mentioned male characters in the process of turning Ophelia into a machine, i.e., a robotic character. The paper delineates the situation of renaissance women under a male-dominated society and highlights the danger of exerting too much pressure on people to a degree that may lead to untoward consequences.